Scaling CO2 Capture With Downstream Flow CO2 Conversion to Ethanol - Pace, Grant; Sheehan, Stafford W. (Frontiers in Climate, 2021)
To prevent the global average temperature from increasing more than 1.5 °C and lower the concentration of greenhouse gases (GHGs) in the atmosphere, most emissions trajectories necessitate the implementation of strategies that include both GHG mitigation and negative emissions technologies (NETs). For NETs, there are unique research challenges faced by both CO2 capture and utilization to scale in an economically feasible manner. Starting with incumbent methods, wherein CO2 is recovered from a high concentration source, and moving toward CO2 capture from more widely available dilute sources, we outline how CO2 capture systems interface with downstream utilization in flow reactors. To provide a real-world point of comparison, we analyze CO2 sourcing for Air Company’s CO2-to-alcohols pilot and demonstration scale deployments in Brooklyn, New York, USA and Calgary, Alberta, Canada as case studies. The degree of reduction in atmospheric CO2 depends on product alcohol usage; for example, use as a fixed chemical feedstock provides longer term emissions reduction than as a fuel, which is eventually oxidized. Lastly, we discuss the barriers that are present for economic scale-up of CO2 capture and utilization technologies broadly.